Comparative transcriptome profile analysis of granulosa cells from porcine ovarian follicles during early atresia - Jinbi Zhang; Xinxin Qin; Caixia Wang; Yuge Zhang; Yizhe Dou; Shiyong Xu; Jingge Liu; Zengxiang Pan (Animal Biotechnology, 2024)
At various stages of ovarian follicular development, more than 99% of follicles will be eliminated through a degenerative process called atresia. The regulatory mechanisms of atresia have been elucidated to some extent, involving hormones, growth factors, cytokines, and other factors. However, the stimuli initiating atresia in follicular granulosa cells remain unknown. In this study, we isolated the granulosa cells from porcine ovarian follicles (3–5 mm diameter) divided into healthy follicles (HFs) and early atretic follicles (EAFs). We applied high-throughput RNA sequencing to identify and compare differentially expressed genes (DEGs) between HFs and EAFs. A total of 31,694 genes were detected, of which 21,806 were co-expressed in six samples, and 243 genes (p < 0.05; FDR < 0.05) were differentially expressed (DEGs), including 123 downregulated and 120 upregulated in EAFs. GO analysis highlighted hormone metabolism, plasma membrane localization, and transporter activity. The pathway analysis indicated that 51 DEGs, involved in steroidogenesis, cell adhesion molecules, and TGF-beta signaling pathways, were highly related to atresia. Additionally, the interaction network of DEGs (p < 0.01; FDR < 0.05) using STRING highlighted LHR, ACACB, and CXCR4 as central nodes. In summary, this transcriptome analysis enriched our knowledge of the shifted mechanisms in granulosa cells during early atresia and provided novel perspectives into the atresia initiation.